2021
DOI: 10.3389/fpsyg.2021.635106
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Value-Based Leadership Behavior at the Frontline of Management: A Role Theory Perspective and Future Research Agenda

Abstract: The importance of value-based leadership such as authentic, ethical, and servant leadership is inconspicuous. However, the benefits of these leadership approaches are often only explained through the behaviors of their followers. As such, limited research has communicated the leader’s motivation for pursuing such leadership behavior, resulting in such discourse to escape theorizing. We draw upon role theory and paid attention to the role of higher-level management (leadership) through the trickle-down model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 229 publications
(316 reference statements)
0
18
0
Order By: Relevance
“…When a leader is engaged in listening to a team member’s needs and cognizant of their wellbeing, the leader may be more flexible and effective at shift schedules and determining daily responsibilities [ 34 , 35 ]. In addition, a component of being an authentic leader, relational transparency, may help team members become more self-reliant and connected to the organization, thereby increasing their engagement in organizational activities and culture, and assuming increased control over their job.…”
Section: Discussionmentioning
confidence: 99%
“…When a leader is engaged in listening to a team member’s needs and cognizant of their wellbeing, the leader may be more flexible and effective at shift schedules and determining daily responsibilities [ 34 , 35 ]. In addition, a component of being an authentic leader, relational transparency, may help team members become more self-reliant and connected to the organization, thereby increasing their engagement in organizational activities and culture, and assuming increased control over their job.…”
Section: Discussionmentioning
confidence: 99%
“…The sociological approach is used to portray women in carrying out their roles in the family. Role theory is a paradigm that considers that a person's daily activities are determined socially according to the role he/she plays, such as the role of mother, the role of wife, and the role of teacher (Chang, Budhwar, & Crawshaw, 2021). Biddle and Thomas believe that there are four indicators related to roles, namely expectations from other people, applicable norms, attitudes towards a role, and evaluation of behavior (Desky, Putri, & Tania, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Lyons (1971) reported that individuals will experience role clarity when having access to unvaried, role-relevant information, and when they experience a feeling of having enough role-relevant information. Obviously, individuals will face role ambiguity when they do not experience role clarity (Smith and Brannick, 1990;Chang et al, 2021), and the resulting role stress may negatively influence their job performance (Miner, 1971;Tubre and Collins, 2000;Wu et al, 2019), in our case, the effective implementation of HR policies.…”
Section: Literature Reviewmentioning
confidence: 95%